The Relationship between Clean and Healthy Living Behavior and Risk of Diarrhea in Toddler - Febriawan, Naufal Rafi’; Khasanah, Uswatun; Yusuf, Ade (Journal of Maternal and Child Health, 2024)
Background: Diarrhea is a process of defecation in which the stool is more liquid which can be accompanied by blood or mucus with the intensity of defecation increasing more than 3 times a day. The occurrence of diarrhea in children is often attributed to inadequate environmental hygiene. This study aimed to examined the relationship between clean and healthy behavior (PHBS) and diarrhea among toddlers in the working area of ​​the Kalijaga Permai Cirebon Community Health Center. Subjects and Method: This was a cross-sectional study conducted at ​​the Kalijaga Permai Cirebon Community Health Center from May to June 2023. A total of 119 mothers with toddlers (aged 0-59 months) was selected for this study. The dependent variable was diarrhea. The independent variable was clean and healthy behavior (PHBS). The data were collected using a questionnaire and analyzed using chi square. Results: Mothers with poor PHBS increased the risk of diarrhea in children by 4.69 times compared to good PHBS (OR= 4.69; 95% CI = 3.04 to 7.24; p<0.001). Conclusion: Implementation of household clean and healthy behavior lower the risk of diarrhea.